2018
DOI: 10.17511/ijphr.2018.i3.03
|View full text |Cite
|
Sign up to set email alerts
|

Computer Professionals and their Health issues and Managements

Abstract: Background:The professionals using computers for more than four hours a day are susceptible to develop problems like computer vision syndrome (CVS), eye strain, shoulder problems, Musculoskeletal disorder, Carpal tunnel syndrome, stress, and neck and shoulder problem and back pain, etc. The current study has proposed to unearth these problems and associated factors with their working environment conditions and pave way for pursuing further researches in this area and bringing policy level changes to for their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A mojority of UUM community usea computer for their routine jobs and activities. Spending many hours using a computer without a break can cause negative effects on users' health.Excessive computer use can lead tomuscle and joint pain, overuse injuries of the shoulder, arm, wrist or hand, and eyestrain [10] [19]. Also, a study by [14] as cited in [18] reported that staring at a bright screen for hours can causeeye fatigue or eye strain, headaches, blurred vision, burning, itching or tearing eyes, and temporary vision disorders.…”
Section: Introductionmentioning
confidence: 99%
“…A mojority of UUM community usea computer for their routine jobs and activities. Spending many hours using a computer without a break can cause negative effects on users' health.Excessive computer use can lead tomuscle and joint pain, overuse injuries of the shoulder, arm, wrist or hand, and eyestrain [10] [19]. Also, a study by [14] as cited in [18] reported that staring at a bright screen for hours can causeeye fatigue or eye strain, headaches, blurred vision, burning, itching or tearing eyes, and temporary vision disorders.…”
Section: Introductionmentioning
confidence: 99%